Analysis of Physical Education Teachers' Readiness in Integrating Digital Literacy into Learning - Ismail, Isnardi (Journal of Salutare, 2025)
The development of digital technology requires Physical Education, Sports, and Health (PJOK) teachers to have qualified digital literacy in order to be able to integrate technology-based media, methods, and evaluations in learning. However, the readiness and ability of PJOK teachers in this aspect is still a challenge that needs to be further researched. This study aims to analyze the influence of PJOK teachers' digital literacy on learning outcomes, learning achievements, student empowerment, evaluation quality, and student motivation and involvement. The method used is Systematic Literature Review (SLR) with 24 articles from reputable national and international journals (2020–2025) selected as the basis for the analysis. Data was analyzed through thematic synthesis to identify the pattern of influence of teachers' digital literacy on various aspects of learning. The results of the study show that PJOK teachers' digital literacy contributes positively to improving learning outcomes, competency achievement, and the quality of learning evaluation, and digital literacy also empowers students to be more independent, increase active participation, and foster intrinsic motivation in learning activities, the implications of this study are the need for sustainable teacher digital literacy training programs, support for educational infrastructure, and policies that are encouraging the integration of technology in PJOK learning in the digital era.